Can Local Participatory Programs Enhance Public Confidence : Insights from the Local Initiatives Support Program in Russia - Shulga, Ivan; Shilov, Lev; Sukhova, Anna; Pojarski, Peter (World Bank, Washington, DC, 2019)
This paper reviews the performance of the Russia Local Initiatives Support Program (LISP) as an instrument for directly addressing the needs of the population to access socioeconomic infrastructure, for increasing public confidence in self-governance frameworks and institutions through dialogue and community budgeting consultations, and for strengthening the capacity for local self-governance. The paper does this by looking at historical and survey data from the implementation of the LISP methodology as part of regional programs in Russia.